PREPARATION OF PAPERS FOR JOURNAL SCIENCES & TECHNOLOGIES A. (Sciences & Technology. A, exactes sciences, 2017)
We present a space-time transformation to the harmonic oscillator with a  time-dependent mass and frequency and we transform the problem to that of constant mass and time-dependent potential of the form  . The propagator and the corresponding wave functions are given.  A new general model of time-dependent mass is proposed.